Assessment of Autogenous Cortical Bone Grafting Combined with Guided Tissue Regeneration for Managing Intraosseous Periodontal Defects - Mohammed Ahsan Razi; Rabia Zarrin; Manisha; Manoj Kumar Singh; Rosy Kumari; Ria Sahay (Journal of Pharmacy and Bioallied Sciences)
Background: In clinical periodontology, treating intraosseous periodontal abnormalities is still difficult. When combined with guided tissue regeneration (GTR), autogenous cortical bone grafting has shown potential for accelerating the regeneration of periodontal tissue. Materials and Methods: This randomized controlled clinical study included 30 individuals with intraosseous periodontal abnormalities that were verified by radiography and clinical examination and were between the ages of 25 and 50 years. Autogenous cortical bone grafts taken from the mandibular ramus were used to correct the deformities, together with a bioresorbable GTR membrane. Clinical parameters were measured at baseline and during the 6-month follow-up, including probing pocket depth (PPD), clinical attachment level (CAL), and defect fill. Before and after treatment, the size of the bone defect was measured using cone-beam computed tomography (CBCT). Results: In the therapy group, significant progress was seen. After 6 months, the mean CAL gain was 3.6 ± 0.6 mm and the mean PPD decrease was 4.2 ± 0.8 mm. The treated locations had a mean defect fill of 68% ± 10%, according to radiographic examination. During the research period, no serious problems were noted, and patients reported little postoperative pain. Conclusion: In the treatment of intraosseous periodontal abnormalities, autogenous cortical bone grafting combined with GTR dramatically enhances clinical and radiographic results.